The Paleoarchean and Mesoarchean TTGs of the western Azov area, the Ukrainian Shield - Artemenko, G.V.; Shumlyanskyy, L.V. (Доповіді НАН України, 2021)
A large anticline structure occurs in the western part of the Azov Domain of the Ukrainian Shield. It is composed
of rocks of the Mesoarchean (3.2-3.0 Ga) granite-greenstone association and relics of an older basement. The anticline
is divided into two parts by the Bilotserkivka structure of sub-latitudinal strike. The northern part includes
the Huliaipole and Remivka blocks, and the southern part comprises the Saltycha anticline. The U-Pb age of plagiogneisses
of the Lantsevo anticline of the Bilotserkivka structure is 3299 ± 11 Ma. In terms of geochemical characteristics,
they correspond to TTGs. In the western part of the Bilotserkivka structure, we previously identified
quartz diorites having an age of 3297 ± 22 Ma. These data show that the Bilotserkivka structure represents an ancient
basement. Dislocated trondhjemites were studied in the Ivanivka area at the eastern part of the Saltycha anticline.
They contain numerous relics of heavily altered amphibolites. The U-Pb age of zircons from trondhjemite is
3013 ± 15 Ma. These rocks are of the same age as TTGs of the Shevchenko Complex cutting through the sedimentary-
volcanogenic rocks of the greenstone structures of the Azov Domain. They share age and geochemical characteristics
with biotite and amphibole-biotite gneisses of the “Kainkulak beds” in the Zrazkove village located at the
Mokra Konka river (3.1-3.0 Ga) and with biotite gneisses in the lower reaches of the Kainkulak river (2.92 Ga).
Thus, gneisses of the “Kainkulak beds” actually represent the Mesoarchean TTGs of the Shevchenko Complex, transformed
in the Paleoproterozoic time due to the dislocation metamorphism. The late Paleoarchean (3.3 Ga) tonalites
are known in the West Azov and KMA domains; they probably also occur in the basement of the Middle Dnieper
domains, where detrital zircons of this age have been reported. These data allow us to assume the existence of a
large Late Paleoarchean (3.3 Ga) protocraton, in which the Mesoarchean (3.2-3.0 Ga) greenstone belts and TTGs of
the eastern part of the Ukrainian Shield and the KMA Domain were formed. У Західній частині Приазовського блока знаходиться велика антиклінорна структура, яка складена породами мезоархейської (3,2—3,0 млрд років) граніт-зеленокам’яної асоціації. Вона розділена Білоцерківською структурою субширотного простягання на дві частини — північну, що включає Гуляйпільський і
Ремівський блоки, і південну — Салтичанський антиклінорій. Визначено, що U-Pb вік плагіогнейсів
Ланцівської антикліналі Білоцерківської структури становить 3299 ± 11 млн років. За геохімічними характеристиками біотитові гнейси відповідають ТТГ. На відстані 30 км у західній частині Білоцерківської
структури раніше нами були виявлені кварцеві діорити такого ж віку — 3297 ± 22 млн років. Ці дані
показують, що Білоцерківська структура є блоком давнього фундаменту. На Іванівській ділянці східної
частини Салтичанського антиклінорію вивчені дислоковані тронд’єміти. Визначено, що U-Pb вік тронд’ємітів 3013 ± 15 млн років. Ці тронд’єміти, таким чином, є одновіковими з ТТГ шевченківського комплексу,
які проривають осадово-вулканогенні породи зеленокам’яних структур Приазовського мегаблока. Пізньопалеоархейські (3,3 млрд років) тоналіти, поширені на Західному Приазов’ї, знайдено також на мегаблоці КМА Воронезького кристалічного масиву, і, ймовірно, вони є у складі гнейсового фундаменту
Серед ньопридніпровського блока, де у Високопільській зеленокам’яній структурі було знайдено кластогенний циркон такого віку. Ці дані вказують на вірогідне існування більш давнього протократону віком
3,3 млрд ро ків, на якому формувалися мезоархейські (3,2—3,0 млрд років) зеленокам’яні пояси східної
частини УЩ і мегаблока КМА.